2018
DOI: 10.3389/fpls.2018.00927
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Phylogenetic Analysis Revealed the Chloroplast Genome Variation and Interspecific Relationships of Corylus (Betulaceae) Species

Abstract: Corylus L. is an economically and phylogenetically important genus in the family Betulaceae. Taxonomic and phylogenetic relationships of Corylus species have long been controversial for lack of effective molecular markers. In this study, the complete chloroplast (cp) genomes of six Corylus species were assembled and characterized using next-generation sequencing. We compared the genome features, repeat sequences, sequence divergence, and constructed the phylogenetic relationships of the six Corylus species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 77 publications
(81 reference statements)
5
42
0
1
Order By: Relevance
“…The cp genomes of most angiosperms are validated to contain approximately 130 genes, of which about 20 genes have two copies in two IRs, leaving the rest 110 being unique genes (Mader et al, 2018;Hu et al, 2017;Xu et al, 2017;Yang et al, 2018). Our annotations are similar to those reported above.…”
Section: Chloroplast Genome Variation and Evolutionsupporting
confidence: 76%
See 1 more Smart Citation
“…The cp genomes of most angiosperms are validated to contain approximately 130 genes, of which about 20 genes have two copies in two IRs, leaving the rest 110 being unique genes (Mader et al, 2018;Hu et al, 2017;Xu et al, 2017;Yang et al, 2018). Our annotations are similar to those reported above.…”
Section: Chloroplast Genome Variation and Evolutionsupporting
confidence: 76%
“…In order to evaluate the sequence divergence of Betulaceae cp genomes, we randomly selected six of the available Betulaceae species (one representative for each of the six genera), including three cp genomes we reported here plus the cp genomes of Carpinus tientaiensis (KY174338), Betula nana (KX703002), and Ostrya rehderiana (KT454094). Based on previous studies, the contraction and expansion of IR regions could bring about the structure variation and length change of cp genomes (Nazareno et al, 2015;Yang et al, 2018). Thus, we performed a comparative analysis to test the variation in the IR/SC junctions among Betulaceae cp genomes.…”
Section: Comparative Analysis and Sequence Divergencementioning
confidence: 99%
“…In our study, both the results from the mVISTA analysis and the nucleotide variability (pi) assessment showed that numerous divergence hotspot regions are primarily situated in the SCs of the cp genome and that more variable sites are located in intergenic regions than in coding genes, and these can be directly utilized for the development of new molecular markers for research on Quercus species identification and taxonomy. Among these divergence hotspot regions, trnH-psbA has already been selected as a suitable barcode for plants [40,73], as have rbcL-accD, trnS-trnG [74], ndhF [40,75], ycf1 [69,76], accD [67,77], trnG-trnR [78] and trnK-rps16 [79]. In this study, the ycf1, ndhF and accD genes were found to be optimal genetic markers based on their high substitution variability, repeat sequence diversity and SSC/IR junction length variability.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, phylogenetic analysis of whole chloroplast genomes was suggested as an alternative to provide better resolution for species designation [ 10 , 11 ]. In support of this, consolidation of alignments for the majority of genes in a plastid genome has been successfully used for building species trees in a number of instances [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%